Characterizing and controlling intrinsic biases of lambda exonuclease in nascent strand sequencing reveals phasing between nucleosomes and G-quadruplex motifs around a subset of human replication origins - Foulk, Michael S.; Urban, John M.; Casella, Cinzia; Gerbi, Susan A. (Genome Research, 2015)
Nascent strand sequencing (NS-seq) is used to discover DNA replication origins genome-wide, allowing identification of features for their specification. NS-seq depends on the ability of lambda exonuclease (λ-exo) to efficiently digest parental DNA while leaving RNA-primer protected nascent strands intact. We used genomics and biochemical approaches to determine if λ-exo digests all parental DNA sequences equally. We report that λ-exo does not efficiently digest G-quadruplex (G4) structures in a plasmid. Moreover, λ-exo digestion of nonreplicating genomic DNA (LexoG0) enriches GC-rich DNA and G4 motifs genome-wide. We used LexoG0 data to control for nascent strand–independent λ-exo biases in NS-seq and validated this approach at the rDNA locus. The λ-exo–controlled NS-seq peaks are not GC-rich, and only 35.5% overlap with 6.8% of all G4s, suggesting that G4s are not general determinants for origin specification but may play a role for a subset. Interestingly, we observed a periodic spacing of G4 motifs and nucleosomes around the peak summits, suggesting that G4s may position nucleosomes at this subset of origins. Finally, we demonstrate that use of Na+ instead of K+ in the λ-exo digestion buffer reduced the effect of G4s on λ-exo digestion and discuss ways to increase both the sensitivity and specificity of NS-seq.